DYSBACTERIOSIS IN CHILDREN - Umarkulov Mukhtorali; Nizamutdinov Avazbek Maripdjanovich (Scholar Express Journals, 2022)
This article presents dysbacteriosis in children. It deals with presentation of dysbacteriosis and its clinical studies.
Keywords: Dysbacteriosis; dysbiosis; SIBO; SIFO